Comparison of Patient Perceptions with Diode Laser and Scalpel Technique for Frenectomy - Bista, Soni; Adhikari, Khushbu; Saimbi, Charanjeet Singh; Agrahari, Bikash (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: Frenum that encroaches on the margin of the gingiva may interfere with plaque removal and can lead to gingival recession and midline diastema. Thus in order to facilitate maintenance of proper oral hygiene and prevention of gingival recession, frenectomy is done. Aim: The aim of this study was to compare the effects of the diode laser and the scalpel technique on the degree of postoperative pain experienced by patients after frenectomy. Materials and Methods: Twenty patients requiring frenectomy were randomly assigned to two treatment groups, one with a diode laser and the other with a scalpel. The postoperative pain of each patient was assessed using a Visual Analog Scale and the number of analgesic used was recorded on postoperative days one and seven. Results: Patients treated with the diode laser had significantly less postoperative pain at day one and used less number of analgesic (2.30 ±0.94) as compared to scalpel surgery (4.40 ±1.07). Conclusion: This comparative study indicates that diode laser treatment for frenectomy provides better patient perception in terms of pain compared to scalpel technique.